2016
DOI: 10.1002/jmri.25450
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of cardiac volumes, dimensions, and new functional parameters by MR: A multicenter, multivendor study

Abstract: 2 J. Magn. Reson. Imaging 2017;45:1055-1067.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 17 publications
5
93
0
Order By: Relevance
“…Biventricular volumes, ejection fraction and mass, as well as atrial volumes were measured by manually tracing the endocardial and epicardial border at end‐ventricular diastole and systole using cine short‐axis images. Previously reported reference values of normality for LV and RV volumes were used …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biventricular volumes, ejection fraction and mass, as well as atrial volumes were measured by manually tracing the endocardial and epicardial border at end‐ventricular diastole and systole using cine short‐axis images. Previously reported reference values of normality for LV and RV volumes were used …”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive MR evaluation was performed following an examination protocol for each CHD as previously published. 13 In particular, biventricular function was assessed by breath-hold, steadystate, free-precession cine imaging in cardiac short-axis, encompassing both ventricles and atria by contiguous 8-mm thick slices (field of view 32-38 cm, repetition time (TR) / echo time (TE) = 2, flip angle 45 , matrix 224 × 224, reconstruction matrix 256 × 256, 30 cardiac phases, views per segment [14][15][16][17][18][19][20][21][22][23][24]. Pulmonary and aortic flow was evaluated using a free-breathing velocity-encoded phase-contrast gradient-echo cine sequence with the following parameters: TR/TE 12/5 msec, flip angle 20 , field of view 30, phase field of view 1, matrix 192 × 192, reconstruction matrix 256 × 256, slice thickness 5 mm, encoding velocity 150-400 cm/s.…”
Section: Magnetic Resonance Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Left ventricular volumes, mass, and EF were measured using a previously validated software (EasyVision, version 4.0; Philips Medical Systems) and categorized in accordance with reference values …”
Section: Methodsmentioning
confidence: 99%
“…Reference values of cardiac MRI dimensions have been proposed. 22 The authors defined LVH according to cardiac MRI measurements based on previously reported and accepted parameters ([ 74 g/m 2 in males and [ 63 g/m 2 in females). 23 Prior research using conventional Anger SPECT cameras demonstrated that LV mass can also be computed from radionuclide MPI studies.…”
mentioning
confidence: 99%